Grey relational analysis of Green Lean Six Sigma critical success factors for improved organisational performance. (6th January 2022) - Rathi, Rajeev; Vakharia, Ammar; Kaswan, Mahender Singh
Green Lean Six Sigma (GLS) is an eco-friendly approach that reduces ecological damages through reduced rejection, wastes, and rework. But it is essential to investigate the success factors of GLS that work as the first line of preparedness for the successful implementation of this sustainable approach. The current research deals with the identification and investigation of GLS success factors. Twenty-three GLS success factors have been identified from the literature pertaining to manufacturing and formulated into eight logical grouped or critical success factors using principal component analysis. The prioritisation of GLS critical success factors has been done through grey relational analysis by considering a case of the manufacturing industry. It has been found that management and finance-related are the most significant critical success factors with grey relational grades 0.6952 and 0.6682, respectively. The present study will facilitate the management of the manufacturing industries to implement GLS through systematic understanding and investigation of associated success factors.